(untitled) (Filološke studije, 2019)
The article is dedicated to the foundations of methods and ways of the research into emotionally-volitional motivation of speech acts. It is accentuated that the studies of speech communication do not have sufficient empirical basis, therefore searching of the new ways of interpretation of speech products from the point of view of participants’ motives, intentions, pragmatic suggestions is one of the urgent problems in the theory of speech communication. The article describes reasonable underlying basis of a certain dialog; the basis is reconstructed in terms of the interlocutors’ “auto-reports” and the interpretations derived from the result of the third persons’ inquiry.